Cellular Site of Escherichia coli Ribosomal RNA Synthesis - Haywood, Anne M. (1971)
Escherichia coli, grown for a generation after the addition of [(14)C]uracil and for one minute after a pulse of [(3)H]uracil, were lysed in the presence of 6 mM Mg(++), and divided into a 30,000 × g “supernatant” and sediment. The sediment was resuspended in buffer containing no divalent cations, and again centrifuged to give the “Mg(++) sediment” and the remaining “sediment”. The ratio of (3)H (one-minute pulse RNA) to (14)C (Stable RNA) in the supernatant is 1/6 to 1/10 that of the sediment RNA, and the ratio of (3)H:(14)C in the Mg(++) sediment is 1/2 to 1/6 that in the sediment RNA. Gel electrophoresis of RNA from the different fractions shows that ribosomal RNA precursors first appear in the sediment. It is concluded that the site of ribosomal RNA synthesis is associated with a sedimentable structure, which is probably cell membrane.